Application of chimeric glucanase comprising mutanase and dextranase for prevention of dental biofilm formation. (January 2015) - Otsuka, Ryoko; Imai, Susumu; Murata, Takatoshi; Nomura, Yoshiaki; Okamoto, Masaaki; Tsumori, Hideaki; Kakuta, Erika; Hanada, Nobuhiro; Momoi, Yasuko
ABSTRACT Water‐insoluble glucan (WIG) produced by mutans streptococci, an important cariogenic pathogen, plays an important role in the formation of dental biofilm and adhesion of biofilm to tooth surfaces. Glucanohydrolases, such as mutanase (α‐1, 3‐glucanase) and dextranase (α‐1, 6‐glucanase), are able to hydrolyze WIG. The purposes of this study were to construct bi‐functional chimeric glucanase, composed of mutanase and dextranase, and to examine the effects of this chimeric glucanase on the formation and decomposition of biofilm. The mutanase gene from Paenibacillus humicus NA1123 and the dextranase gene from Streptococcus mutans ATCC 25175 were cloned and ligated into a pE‐SUMOstar Amp plasmid vector. The resultant his‐tagged fusion chimeric glucanase was expressed in Escherichia coli BL21 (DE3) and partially purified. The effects of chimeric glucanase on the formation and decomposition of biofilm formed on a glass surface by Streptococcus sobrinus 6715 glucosyltransferases were then examined. This biofilm was fractionated into firmly adherent, loosely adherent, and non‐adherent WIG fractions. Amounts of WIG in each fraction were determined by a phenol‐sulfuric acid method, and reducing sugars were quantified by the Somogyi–Nelson method. Chimeric glucanase reduced the formation of the total amount of WIG in a dose‐dependent manner, and significant reductions of WIG in the adherent fraction were observed. Moreover, the chimeric glucanase was able to decompose biofilm, being 4.1 times more effective at glucan inhibition of biofilm formation than a mixture of dextranase and mutanase. These results suggest that the chimeric glucanase is useful for prevention of dental biofilm formation.